BS ISO 965-5 AMD1. ISO general purpose metric screw threads. Tolerances. Part 5. Limits of sizes for internal screw threads to mate with hot-dip galvanized external screw threads with maximum size of tolerance position h before galvanizing (29th September 2020) - British Standards Institution,
No abstract available